Implementasi metode promethee dalam sistem pendukung keputusan penilaian kinerja dosen - da Costa Fátima, Manuela Rosa; Lobo Soares, Jaime da Costa (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
Lecturers are a key element in improving the quality of education in higher education. Effective assessment of lecturer performance is essential for evaluation and improvement of education quality. Instituito Profissional de Canossa (IPDC) evaluates lecturer performance through manual methods involving students, this process often produces inaccurate data and slows down decision making. For this reason, a decision support system is needed that can accommodate all the criteria needed in decision making using the promethee method to assess lecturer performance. Promethee was chosen in this research because of its ability to consider data characteristics and provide more accurate results. This DSS will consider three assessment criteria, including education, community service and research. The results of the DSS implementation with the Promethee method can provide recommendations for lecturer performance rankings that help the quality assurance team in identifying outstanding lecturers.